Athenagorae qui fertur De resurrectione mortuorum - Marcovich, Miroslav, 1919-2001.; Athenagoras, active 2nd century. (Vigiliae Christianae, Supplements, 2000)
This monograph comprises a new critical edition of Ps.-Athenagoras De Resurrectione Mortuorum , a complete edition of Arethas' Scholia on the treatise, and (in the Appendix) a critical edition of the extant fragments of De Resurrectione attributed to Justin Martyr. Athenagoras was a Christian apologist, who flourished in the second half of the second century CE (ca. 180). Traditionally two extant Greek works have been attributed to him: a Plea on Behalf of the Christians , probably addressed to the Roman emperors Marcus Aurelius and Commodus, and the On the Resurrection of the Dead . The attribution of the latter treatise to Athenagoras has been a matter of dispute. In his Introduction, the editor sides with those scholars denying Athenagoras' authorship, but ascribes its date to the end of the second century. This important edition by one of the most esteemed scholars in the field complements Prof. Marcovich's edition of Athenagoras Legatio pro Christianis (Berlin, 1989).